Sulfamethoxazole-trimethoprim associated with resveratrol for the treatment of toxoplasmosis in mice: Influence on the activity of enzymes involved in brain neurotransmission - Bottari N.B. (2015)
© 2015 Elsevier Ltd.This study aimed to investigate the influence of sulfamethoxazole-trimethoprim (ST) associated with resveratrol on the enzymatic activities of acetylcholinesterase (AChE), adenylate kinase (AK), pyruvate kinase (PK), and creatine kinase (CK) in the brain of mice experimentally infected by Toxoplasma gondii. For that, 60 mice were divided into ten groups with 6 animals each: groups A to D composed by healthy mice and groups E to J consisting of animals infected by T.gondii (VEG strain). Animals started treatment 20 days post-infection for 10 consecutive days with oral doses of 0.5mgkg-1 of ST (groups B and F), 100mgkg-1 of free resveratrol (groups C and G) and inclusion complex of resveratrol (nanoparticles containing resveratrol) (groups D and H), as well as with an association of both drugs (groups I and J). The results showed increased (P<0.001) AChE activity on infected animals (groups E-J) when compared to not-infected (A) animals, and also uninfected animals treated with ST (group B) had increased AChE activity. AK activity decreased (P<0.001) in the infected and untreated (group E), differently from the other groups that did not differ. PK activity did not differ between groups (P>0.05). When comparing control groups (uninfected (A) and infected (E)), we verified a significant (P<0.001) increase in CK activity in the brain, and it is noteworthy that the animals treated with resveratrol associated with ST (group I and J) had similar CK activity to those animals from the group A. Treatment with the combination of ST and resveratrol was able to reduce (P<0.05) the number of parasitic cysts in the brain, thus reduced inflammatory infiltrates in the liver, and prevented the occurrence of hepatocytes lesions due to toxoplasmosis in mice. Based on these results, it is possible to conclude that increased AChE and CK activities after T.gondii infection did not change with the treatment of ST-resveratrol association. In addition, decreased AK activity caused by T.gondii infection was normalized by ST-resveratrol treatment. T.gondii infection and treatment does not affect PK activity in brain.